Buildings at Park Square, ca. 1925 - Lawrence, George E. (Tufts Archival Research Center, 2005)
Elevated view southeast of the south-southwest elevation of the Sewlyn Theatre and a neighboring building, both of which are located on Columbus Avenue at Park Square. Several automobiles fill the service station, which is visible in the lower-half of the photograph. Signage adorns both buildings. Several men are included in the photograph. 7 1/4 x 9 1/2 Photographs